Psychological profiling of young female handball and basketball players – a pilot study. Issue 4 (27th March 2011) - Shima, Y; Kitaoka, K; Nakase, J; Goshima, K; Takahashi, R; Tsukagoshi, S; Yoneda, Y; Moriyama, S; Ogawa, Y; Tsuchiya, H
Abstract : Background: The influence of psychological factors on injuries in female handball and basketball is poorly documented. Objective: The aim of this study was to examine the influence of psychological factors on injuries in female handball and basketball players, especially for non-contact anterior cruciate ligament (ACL) injuries. Design: Case control study. Setting and Participants: A three-year prospective cohort study has been initiated in Japanese young female handball and basketball players to identify risk factors for non-contact ACL injuries. At baseline, 99 of 104 young female players (handball: 30 players, basketball: 69 players, age;15–16 years) were asked to complete a detailed questionnaire covering player history, previous injuries, KOOS, personality and psychological-competitive ability using the Y-G personality questionnaire and questionnaire for diagnostic inventory of psychological-competitive ability score (DIPCA-3). Results: There were no correlation between KOOS and DIPCA-3, and no significant differences were found between handball players and basketball players. There were no significant differences between previously injured and non-injured players in the score of KOOS and DIPCA-3. The players evaluated as D (director) type by the Y-G personality questionnaire scored significantly better result in DIPCA-3 than the A (average), B (burst), E (engineer) type (p=0.0128, p=0.001, p<0.001, respectively). Conclusion: Since perceived mastery climate has been reported as a significant predictor for new injuries, the players who has high psychological-competitive ability evaluated as D type may be the injury-prone athletes. Prospective follow-up is necessary to elucidate whether high psychological-competitive ability is a risk factor for ACL injury or new injury.